Living elegiacally: the temporality of tragedy in Friedrich Hölderlin - Kerkhoff, Manfred (Estudios de Filosofía, 1994)
The interest of the article is two fold: Holderlin’s poetics, especially his theory of tragedy, and, on part of the author, a kairologically oriented philosophical consideration which aims at taking distance from the philosophy of history. The tragical conception of the world is investigated in Holderlin ’s versions of Hyperion and Empedocles; the historical dimension of poetic activity is studied in his translations of Sophocles’ Oedipus and Antigdne; the tragical conception of history appears in the interpretati6n of the poem Pathmos. The author’s interest is centered on the question of time, not in its conceptual generality, however, but rather on understanding it as event, being "adequate time".